The demographic challenge in Castilla y León (Spain): an unbalanced region with an aged population - Vidal Domínguez, María Jesús; Fernández Portela, Julio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Castilla y León is a region with demographic features different from other Spanish areas. It is characterized by the loss of demographic numbers, the unequal distribution of its inhabitants, the emptying and masculinization of the rural environment and strong aging. All these issues that have been occurring since the mid-twentieth century are considered a priority in the national policy of the demographic challenge that requires new responses from the political action and change the look towards this territory.